Corporate Mindfulness and Productivity: A Bibliometric Analysis of Mindfulness Practices in HR Strategies - Judijanto, Loso; Usup, Usup; Pahrijal, Rival (Westscience Press, 2025)
This study conducts a bibliometric analysis to explore the intellectual landscape and thematic evolution of mindfulness practices in corporate human resource (HR) strategies, with a particular focus on their relationship to employee productivity and well-being. Drawing data exclusively from the Scopus database, the study utilizes VOSviewer to visualize co-occurrence networks, author collaborations, and international research contributions. The results indicate that “mindfulness” and “human resource management” are central, frequently linked with themes such as stress management, leadership, job satisfaction, and mental health. Temporal trends reveal a shift from individual therapeutic benefits to system-level applications in strategic HR practices. Prominent scholars such as Kabat-Zinn, Brown, Schaufeli, and Bakker anchor different intellectual clusters, while countries like the United States, United Kingdom, and Australia dominate in research production and collaboration. The findings highlight the increasing institutionalization of mindfulness as an HR tool for cultivating well-being, engagement, and sustainable organizational performance. This study not only synthesizes existing scholarship but also identifies key gaps and future research opportunities in integrating mindfulness into contemporary HR strategies.